Abatement of dichloromethane with high selectivity over defect-rich MOF-derived Ru/TiO2 catalysts. Issue 42 (4th October 2022) - Chai, Shaohua; Li, Shuangde; Zhang, Le; Fan, Guijun; Nie, Linfeng; Zhou, Xin; Yang, Wuxinchen; Li, Weiman; Chen, Yunfa
Abstract : The distinction of dechlorination over activation sites with the aid of Ru/TiO2 catalysts derived from MOFs. Abstract : The regulation of oxygen vacancies and Ru species using metal–organic frameworks was synergically adopted in a rational design to upgrade Ru/TiO2 catalysts, which are highly active for the catalytic oxidation of dichloromethane (DCM) with less undesired byproducts. In this work, Ru/M-TiO2 and Ru/N-TiO2 catalysts were synthesized by the pyrolysis of MIL-125 and NH2 -MIL-125 incorporated with Ru, the existence of Ru nanoclusters and nanoparticles was detected by XAFS, respectively, and the catalytic performance was analyzed comprehensively. Complete oxidation of DCM was obtained at ∼290 °C over Ru/M-TiO2 and Ru/N-TiO2 catalysts, while Ru/N-TiO2 showed quite less monochloromethane (MCM) and higher CO2 yields, and better dechlorination capacity in oxidation. The distinction comes down to that the easier desorption of chlorine could be achieved over Ru 4+ which act as the main activated adsorption sites for DCM in Ru/N-TiO2, compared to oxygen vacancies that serve as the main dissociation sites in Ru/M-TiO2 . Additionally, Ru/N-TiO2 exhibited superior stability and excellent resilience in moisture. An in situ DRIFTS experiment further indicated the different DCM catalytic degradation process as well as the reaction mechanism over the as-prepared catalysts.